Out of our archives – the first percutaneous coronary intervention performed on the patient with acute myocardial infarction 26 years ago. A clinical case report. - Igor Kranjec (Zdravniški Vestnik, 2015)
A clinical case of a patient that suffered from an acute myocardial infarction with ST-segment elevation (STEMI) 26 years ago is presented. Systemic thrombolysis was not possible due to the recent bleeding from the duodenal ulcer. Therefore, the urgent percutaneous coronary revascularization, the first such procedure in Slovenia, was successfully carried out. The PCI was successful, the hospital course uneventful, and the patient did not experience any symptoms for the next two years. Unfortunately, the coronary atherosclerosis progressed later due to unsatisfactory secondary prevention measures; however, the treated infarct-related artery remained patent. The authors explain the strategy of the performed percutaneous procedure and discuss the further development of the treatment. Eleven years later, the primary PCI developed into the dominant reperfusion strategy of the STEMI in Slovenia.